Continued outpatient oncology care for cancer survivors by antineoplastic medication use: Identifying opportunities for stratified survivorship care. Issue 28 (1st October 2022) - Birken, Sarah A; Peluso, Alexandra; Wagi, Cheyenne; Shalowitz, David I; Isom, Scott; Bell, Ronny A.; Strom, Carla; Dharod, Ajay; Bundy, Richa; Weaver, Kathryn E.
Abstract : 226 Background: Cancer survivors may be more likely to receive preventive care services when they see both oncologists and PCPs; however, some oncology visits may not be necessary, straining limited subspecialty resources. In this study, we quantified outpatient primary and oncology care utilization in the years surrounding cancer diagnosis. We further characterized the proportion of survivors with oncology visits in the absence of ongoing antineoplastic use, as we hypothesized these survivors might be appropriate for need- and risk-stratified survivorship care, a model successful outside the US. Methods: We conducted a retrospective review of the electronic health records of survivors in an academic health center diagnosed with breast, colorectal, or uterine cancer between 1/1/14 and 9/1/19. We excluded survivors who died during the study period, had a PCP outside of our health system, or had recurrent cancers. Descriptive statistics described survivors' provider visits up to 4 years before and 8 years after diagnosis with their most recent cancer. We then stratified our results by current antineoplastic prescription. Results: Our sample included 1, 929 survivors (75.0% white, 20.1% Black, 5.0% other; 86.2% female; cancer type: 59.4% breast, 26.7% colorectal, 13.8% uterine). In the first-year post-diagnosis, 94.6% of survivors had an oncology provider visit; the figure declined to 55.8% by year 8. The percentage of survivors with PCP visits increased from 41% 3-4 years pre-diagnosis to 66% in year 1 and remained at > 50% 8 years post-diagnosis. More than 50% of survivors saw both PCPs and oncologists through 5 years post-diagnosis. Survivors were slightly more likely to have an oncology visit if they were on antineoplastics; 5+ years after diagnosis, >50% of survivors not on antineoplastics had oncology visits. Conclusions: A slight majority of 5+ year survivors, regardless of antineoplastic use, continue to have oncology visits and may be candidates for discontinuing oncology care. Work is needed to develop and test interventions to facilitate need- and risk-stratified survivorship care focused on transitioning longer-term survivors not on antineoplastics to PCPs.